Is there a “European Paediatrics”? - Dornbusch, Hans Jürgen; Kurz, Ronald; del Torso, Stefano; Hadjipanayis, Adamos; Tenore, Alfred (Frontiers in Pediatrics, 2024)
Children and adolescents, who make up almost 20% of the European population, present particular health issues and frequently unmet needs. Comprehensive care of this vulnerable age group requires specific expertise and continuous advocacy. Over the last sixty years, three major European organisations have been created that have dedicated their activities to supporting these goals. The oldest of the three is the European Academy of Paediatrics (EAP), founded in 1961 as the "Confederation of European Specialists in Paediatrics" (CESP). The EAP aims to advocate, promote, and set standards for achieving the highest quality of care for European children and adolescents through the education and training of paediatricians and the practice of evidence-based medicine. Headquartered in Brussels, the EAP, through the European Board of Paediatrics (EBP), represents the "Paediatric Section" of the "European Union of Medical Specialists" (UEMS-SP), providing educational guidelines and training opportunities, as well as being involved in numerous initiatives related to the health and wellbeing of children and adolescents and research projects funded by the EU Commission.